Psychological and educatory service to facilitate sporting agenda formation in adolescents in sport training process - Cherepov, E. A.; Kalugina, G. K.; Khafizova, A. S. (Theory and Practice of Physical Culture, 2019)
The study makes an attempt to facilitate formation of a theoretical and practical awareness of the potential sport careers in adolescents, with the sport practices viewed as a potential foundation for future sport careers. We used the L.N. Sobchik Children`s Questionnaire Test data obtained for the last 8 years to classify and analyze the group standards and individual personality qualities and their interactions in the adolescent groups to understand the systemic personality development trends in the national adolescent population. Some personality qualities including the spontaneous reactivity, rigidity, introversion and emotional volatility were proved to be the most susceptible to positive transformations in adolescents. The study data and analyses demonstrate that sport trainings in adolescent age may evolve into the core personal life mission when they are (1) unregulated too strictly and driven by fair reality-shaping values and priorities; (2) appealing for and appreciated by the relevant social groups; (3) expressly demonstrative for and appreciated by the supporters/ spectators; and (4) associated with the peer communication, friendship, good motivations and self-assertion aspects of great importance for the age group.